TINGKAT PENGETAHUAN IBU TENTANG AKUPRESUR PADA BAYI DAN BALITA - Roudhotul Jannah, Siti Roudhotul; Azizah, Ninik; Rahmawati, Vivin Eka (Jurnal EDUNursing, 2023)
A healthy baby is expected to grow into a healthy child. This depends on how to care for and pay attention to the baby's development both physically, emotionally and brain development. Direct interaction such as massaging, caressing, and inviting jokes can be one way to stimulate baby's development. Objective: To assess the level of knowledge of mothers about acupressure in infants and toddlers Methods: Descriptive research with a population of 55 respondents and sampling of all mothers who have babies and toddlers. The data analysis used was univariate analysis. Results: Most of the respondents were aged between 20-35 years (49.1%) and most of the respondents' last education was high school (43.6%). Most of the respondents' occupations were self-employed (65.5%), most of the respondents had received information about acupressure on toddlers (72.7%). Conclusion: Most of the respondents have good knowledge. Therefore, it is necessary for the role of health workers to further activate information about acupressure in infants and toddlers and to be able to do acupressure independently. Keywords: Acupressure, Babies, Healthy child.